2021
DOI: 10.1371/journal.pone.0252418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pegbovigrastim on clinical mastitis and uterine disease during a full lactation in grazing dairy cows

Abstract: In this randomized controlled trial on four commercial grazing dairy farms, we investigated whether pegbovigrastim (PEG) treatment affects clinical mastitis (CM) and uterine disease (i.e. retained placenta (RP), metritis and endometritis) occurrence during a full lactation. The association of prepartum body condition score and prepartum non-esterified fatty acid (NEFA) concentration with disease occurrence was also evaluated. Holstein cows were randomly assigned to one of two treatments: first PEG dose approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
3
8
0
Order By: Relevance
“…Recently, we showed that treatment with PEG prevented the negative association of prepartum NEFA concentration with postpartum neutrophil counts (Barca et al, 2021a). In addition, we found that PEG reduced the occurrence of a first case of CM during the first 30 DIM, particularly in cows with elevated prepartum NEFA concentrations and in cows with excessive prepartum BCS (Barca et al, 2021b).…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Recently, we showed that treatment with PEG prevented the negative association of prepartum NEFA concentration with postpartum neutrophil counts (Barca et al, 2021a). In addition, we found that PEG reduced the occurrence of a first case of CM during the first 30 DIM, particularly in cows with elevated prepartum NEFA concentrations and in cows with excessive prepartum BCS (Barca et al, 2021b).…”
Section: Introductionmentioning
confidence: 63%
“…Kaplan-Meier univariable analyses were performed to evaluate the association of CM, RP, metritis, and endometritis with the outcomes of interest. Because RP and metritis occur sequentially and close together in time, and we have previously detected a strong association between these uterine diseases (Barca et al, 2021b), we also grouped them in a new category recorded as uterine disease (UD, i.e., a cow with a record of RP, metritis, or both). In case that RP and metritis were simultaneously associated with an outcome of interest, we evaluated UD, and if it was also associated with the outcome of interest, we used UD only.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations